Religious identity, public goods and centralization: Evidence from Russian and Israeli cities - Theocharis Grigoriadis; Benno Torgler (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2013)
In this paper, we analyze the effects of religious identity - defined both as personal identification with a religious tradition and institutional ideas on the provision of public goods - on attitudes toward central government. We explore whether citizens belonging to collectivist rather than individualist religious denominations are more likely to evaluate their central government positively. Moreover, we explore whether adherence to collectivist norms of economic and political organization leads to a positive evaluation of central government. Surveys were conducted in Russia and Israel as these countries provide a mosaic of three major world religions - Judaism, Eastern Orthodoxy and Sunni Islam. The information gathered also allows us to study whether attitudes towards religious institutions such as the Russian Orthodox Church, the Chief Rabbinate in Jerusalem, the Jerusalem Islamic Waqf, and the Greek-Orthodox Patriarchate of Jerusalem in Israel are able to predict positive attitudes toward centralized forms of governance. We find strong support for the proposition that collectivist norms and an institutional religious identity enhance positive attitudes towards central government.
Keywords: P16; P17; P21; P35; P51; P52; Z12; 330; Religious identity; public goods; collectivism; individualism; local government; centralization; Russia; Israel